BENTHIC FORAMINIFERA ASSOCIATED WITH THE ZOOXANTHELLATE CORAL CLADOCORA IN THE PLEISTOCENE OF THE KOS ISLAND (AEGEAN SEA, GREECE): SEA LEVEL CHANGES AND PALAEOENVIRONMENTAL CONDITIONS - Drinia, H.; Koskeridou E., Koskeridou E.; Antonarakou A., Antonarakou A.; Tzortzaki, E. (Bulletin of the Geological Society of Greece, 2010)
A Pleistocene section, cropping out in the northern Kos Island has been selected for study. The main lithology (clayey sands, sandy marls) of the section is interrupted by a prominent Cladocora bank which allows a proper extraction of its faunal contents and identification at species level. The evaluation of benthic foraminiferal assemblages from this bank helps to determine the range of the environmental controls in sedimentation. The foraminiferal assemblage is related to a relatively high supply of organic material and rather strong current intensities in water depth of the coral growth. We suggest that the fossil reef of Cladocora grew in coastal waters characterised by a marked seasonality, with periodical inputs of terrigenous sediments, moderate turbidity and higher temperature than today. Such results, although preliminary, suggest that Cladocora together with benthic foraminifera could be reference species for future work on changing Mediterranean climate and sea level.